Characterization of Magnetic Resonance Images for Spinal Cord Tumors - Chung, Jae Yoon (Korean Society of Spine Surgery, 2008)
STUDY DESIGN: Retrospective study MR images for spinal cord tumors. PURPOSE: To analyze the characteristics of MR images for spinal cord tumors, which were then verified at surgery or biopsy. OVERVIEW OF LITERATURE: MR images are often used as the primary diagnostic imaging tool and the preoperative study of choice. The need for biopsy may be obviated because of increasingly accurate preoperative histologic diagnosis by MR images. METHODS: The study group consisted of 39 patients who had undergone MR imaging for preoperative evaluation of spinal cord tumors between September 1989 and February 2008. All patients had operations for spinal cord tumors, which were confirmed at biopsy. Of the 39 patients, 18 were men, and 21 were women. The average follow-up period was 23.8 months. The mean patient age was 46.6 years. RESULTS: Diagnoses included neurilemmoma (19 cases), neurofibroma (4 cases), meningioma (5 cases), hemangioma (3 cases), giant cell tumor (1 case), ganglioneuroma (1 case), lymphoma (1 case), neuroblastoma (1 case), and metastatic tumor from the prostate (1 case). The remaining 3 cases were composed of arachnoid cysts (2 cases) and a vascular malformation (arteriovenous malformation, 1 case). CONCLUSIONS: MR images are the preoperative modality of choice in the evaluation of spinal cord tumors. MR images can narrow the differential diagnosis and guide surgical resection.